The aroma of goat milk: seasonal effects and changes through heat treatment - Siefarth, Caroline; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2014)
Goat milk was characterized and analyzed by human sensory evaluation and gas chromatography/olfactometry (GC/O). Most potent odor-active compounds were determined in (a) raw goats milk from two different seasons and (b) heated goats milk after different treatment intensities. A trained panel found sensorial differences between winter and summer milks (seasonal effect) and milks from different farms (farm-specific effect). A total of 54 odor-active compounds with flavor dilution (FD) factors ≥8 were detected of which 42 odorants were identified. 4-Ethyloctanoic acid, 3-methylindole (skatol) and one unknown compound (RI 2715) showed highest intensities in all raw milks. With heat treatment, goat-like, stable-like, and (cooked) milk-like odor characteristics decreased while caramel-like or vanilla-like notes increased. In total, 66 odor-active compounds were detected in heated goat milks (FD ≥ 8). To the best of our knowledge, only 16 of the 42 identified odorants were reported before in raw goats milk. Additionally, for the first time the presence of 1-benzopyran-2-one (coumarin) could be confirmed in ruminant milk.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.thearo
Keywords: aroma extract dilution analysis (AEDA); aroma profile analysis (APA); fatty acids; mass spectrometry; retention indices; two-dimensional gas chromatography/olfactometry (2D-GC/O)